(untitled) (Journal Of Educational and Psychological Researches, 2016)
Heuristic Program proposal for the treatment of talented emotional and Cognitive problems . 1-The Curtent research aims : to identify the needs of gifted students and their problems and Ways to diagnose . 2-reprepare aproposal heuristic program for the treatment of emotional and Cognitive talented problems . Research . Methodology : analytical and descriptive . Define the terms Virt uoso is the per for mance of the privileged Mstmrave performances appear in any area of his Values . Chapter ll : Includes recipes gifted child and Methods diagnosis gifted by filtrontion and standavds of personal and mental and behavioral Doramwaliman and parental Features and Leader in the detection of the gifted Chapter lll : includes talented emotional problems the casues and talented and Cognitive casuses problems . Chapter IV : includes heuristic program to reduce depression sadness anger , anxiety and stress . The Methods of collective guidance include : role playing – Modelling – feedback household aloajpat list Application of the Beck depression .